Dismetria de membros inferiores: uma breve revisão - Ana Filipa Coelho Queirós (2018)
Leg length discrepancy (LLD), defined as a length difference between the two lower limbs, is a common orthopedic condition with a 70% prevalence in the geral population. Minor LLD is considered a normal variation and has no significant clinical manifestations, however a discrepancy greater than 1 cm can potentially cause altered biomechanics, affecting gait and standing posture. These compensation mechanisms can lead to scolioses, lower back pain and premature degenerative arthritis of the lower extremity and lumbar spine. The management of this deformity varies from no treatment to extensive multistage reconstruction, depending on the severity of the inequality and the function of the limb. Therefore, in children, the assessment of minor LLD growth pattern is fundamental to manage and predict the discrepancy's severity in the mature skeleton. This review aims to consolidate the current information about the classification, etiology and complications of LLD, summarize the various clinical and imaging methods for assessing discrepancy and presenting the treatment protocols.